Corpo, câmera e ação: oficinas de experimentação audiovisual com estudantes de ensino médio - Silva, Eduardo Luiz Corrêa da (Universidade Federal de São Carlos, 2019)
This work is a reflection on the corporate and sonorous productions of students that appear in audiovisual devices during a semester in a discipline called Audiovisual Food Workshops. Reports on the formation of the body as practical, historical, cultural and social in distinct contexts are developed by space and time. We adopted the bibliographic research The chance to perceive different forms of production of the body. Historiographical research grounded the production of audiovisual images, conducting student workshops, allowing them to produce points of view and approaches, so that they could construct a creative and fabulous relationship with their daily lives. And from this perspective, audiovisual devices can respond to sensitive experience and act in a way that liberates discourses, understandings and possibilities of the world. After the realization and interpretation of the material produced in the Workshops, we were able to observe the use of audiovisual materials in school to help transform the processes in their teaching and development contexts about their forms of expression and feel the world.
Keywords: Educação; Corpo; Experimentação audiovisual; Estudos da imagem; Education; Body; Audiovisual experimentation; Image studies; Educación; Cuerpo; Experimentación audiovisual; Estudios de la imagen; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO